CONTENIDOS Y ESTRUCTURA DE UN CONCEPTO "RUSO" EN LA CONCIENCIA DEL LENGUAJE DE LOS TAJIKS - Fisenko, Olga; Tazheva, Zalina; Masyuk, Marina (Revista Inclusiones, 2018)
In article, the concept "Russian" in language consciousness of Tajiks is modelled. Method of a research is the directed associative experiment. The research was conducted based on the Russian-Tajik (Slavic) University. It was proved that the concept "Russian" in the Tajik language recognition has volume lexical structure. The concept "Russian" has the concentrated main zone.